A multivariate geostatistical approach for landscape classification from remotely sensed image data - Vallejos, Ronny; Mallea, Adriana; Herrera, Myriam; Ojeda, Silvia María (2022)
Fil: Vallejos, Ronny. Universidad Técnica Federico Santa María. Departamento de Matemática; Chile.